English Students Reading Interest by Using Literary Reading - Kiki Andriyani; Agung Suhadi; Dian Susyla; Ria Anggraini (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study was to determine the level of reading interest and the factors that influence the reading interest of fourth and sixth semester students of English Education Study Program of Muhammadiyah University of Bengkulu towards literary reading. Therefore, this research method is qualitative research. This research uses a qualitative approach by using descriptive qualitative. Data were obtained through questionnaires and interviews. The questionnaire is to find out the level of students' reading interest in literary reading, while the interview is to get more in-depth information related to students' reading interest in literary reading. The subjects of this study were fourth and sixth semester students of English Education Study Program totaling 40 students as respondents for questionnaires and from the 40 students, 10 students were taken as informants for interviews. From the results of the study, the researcher found that the average student reading interest level was quite high with the following details: 8 (20%) students got the “Low” category, 26 (65%) students got the “Medium” category, and 6 (15%) students got the “High” category. Meanwhile, the results of the study through interviews found more in-depth information on factors affecting student reading interests, namely: Building knowledge of reading literacy, willingness to read, the role of literary reading, personal interests, and the benefits of literary reading. Students state that reading literary works can add to their knowledge of reading, hone creativity, and can also hone them to think critically. Therefore, it is a factor that affects the high interest in reading students in the fourth and sixth semester, so students still familiarize themselves to read literary works. Keywords: Reading Interest, English Students, Literature